Regulation of atherosclerotic plaque inflammation. (November 2015) - Bäck, M.; Weber, C.; Lutgens, E.
Abstract: The immune reactions that regulate atherosclerotic plaque inflammation involve chemokines, lipid mediators and costimulatory molecules. Chemokines are a family of chemotactic cytokines that mediate immune cell recruitment and control cell homeostasis and activation of different immune cell types and subsets. Chemokine production and activation of chemokine receptors form a positive feedback mechanism to recruit monocytes, neutrophils and lymphocytes into the atherosclerotic plaque. In addition, chemokine signalling affects immune cell mobilization from the bone marrow. Targeting several of the chemokines and/or chemokine receptors reduces experimental atherosclerosis, whereas specific chemokine pathways appear to be involved in plaque regression. Leukotrienes are lipid mediators that are formed locally in atherosclerotic lesions from arachidonic acid. Leukotrienes mediate immune cell recruitment and activation within the plaque as well as smooth muscle cell proliferation and endothelial dysfunction. Antileukotrienes decrease experimental atherosclerosis, and recent observational data suggest beneficial clinical effects of leukotriene receptor antagonism in cardiovascular disease prevention. By contrast, other lipid mediators, such as lipoxins and metabolites of omega‐3 fatty acids, have been associated with the resolution of inflammation. Costimulatory molecules play a central role in fine‐tuning immunological reactions and mediate crosstalk between innate and adaptive immunity in atherosclerosis. Targeting these interactions is a promising approach for the treatment of atherosclerosis, but immunological side effects are still a concern. In summary, targeting chemokines, leukotriene receptors and costimulatory molecules could represent potential therapeutic strategies to control atherosclerotic plaque inflammation.